Tobacco Excise Tax Increase Among Health Groups Recommendations To Clinton/Congress (Tufts Archival Research Center, 2007)
Press release from Coalition on Smoking OR Health announcing three recommendations to Congress and President-elect Clinton. Urges Congress and Clinton to increase the tobacco excise tax, pass legislation granting authority to the FDA to fully regulate tobacco products, and to pass comprehensive clean indoor air legislation, including a ban on workplace smoking. Provides experts’ comments on health and the economic effects of smoking.